ASEAN-China Security Relations: Traditional and Non-Traditional Aspects - Ali Abdullah Wibisono (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2017)
Both ASEAN and China used the concept of Non-Traditional Security (NTS) in order to pursue security diplomacy in the Asia Pacific. For ASEAN, NTS is an area of security cooperation that allows it to drive the agenda of security architectures involving extra-regional powers such as the ASEAN Defense Ministerial Meeting Plus (ADMM+) and ASEAN Regional Forum (ARF). For China, NTS policy agenda allows it to gain acceptance among ASEAN member-states and an active role in the security agenda of ASEAN-led security architectures. The question that this article is pursuing is to what extent has ASEAN-China cooperation on NTS balanced between addressing the humanitarian aspect and the political objectives of security? This question is derived from the conceptual origin of NTS that stands on the importance of both the state and the individuals as the referent subjects of security. This article argues that ASEAN-China NTS cooperation emphasized more towards the strengthening of state’s capacity to deal with non-state actors’ transnational criminal activities, either for profit-seeking or subversive purposes. It is also apparent from evaluating the Memorandum of Understandings and Plans of Action between ASEAN and China that NTS cooperation is one China’s investments to engage a closer cooperation with ASEAN as well as a stronger presence in Southeast Asia’s strategic environment.